2006
DOI: 10.1101/gad.1463206
|View full text |Cite
|
Sign up to set email alerts
|

p63 regulates proliferation and differentiation of developmentally mature keratinocytes

Abstract: p63 is a multi-isoform p53 family member required for epidermal development. Contrasting roles for p63 in either the initial commitment to the stratified epithelial cell fate or in stem cell-based self-renewal have been proposed. To investigate p63 function in a post-developmental context, we used siRNAs directed against p63 to down-regulate p63 expression in regenerating human epidermis. Loss of p63 resulted in severe tissue hypoplasia and inhibited both stratification and differentiation in a cell-autonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
534
5
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(586 citation statements)
references
References 26 publications
41
534
5
5
Order By: Relevance
“…In fact, it has been shown that the blockade of cell proliferation due to lack of p63, is p53-dependent. Consistently, p53 down regulation rescues the cell proliferation defect due to a p63 knockdown, but not the incapacity of p63-less cells to differentiate [29,30]. An additional signaling pathway playing a crucial role in epidermal stratification and keratinocytes differentiation is through Notch [39][40][41][42][43].…”
Section: Transcriptional Activities Of P63 Isoformsmentioning
confidence: 63%
See 3 more Smart Citations
“…In fact, it has been shown that the blockade of cell proliferation due to lack of p63, is p53-dependent. Consistently, p53 down regulation rescues the cell proliferation defect due to a p63 knockdown, but not the incapacity of p63-less cells to differentiate [29,30]. An additional signaling pathway playing a crucial role in epidermal stratification and keratinocytes differentiation is through Notch [39][40][41][42][43].…”
Section: Transcriptional Activities Of P63 Isoformsmentioning
confidence: 63%
“…Simultaneous knockdown of p53 in the context of p63 loss is able to rescue cell proliferation, however the differentiation defect is still present [29]. These data [27,29] are therefore somewhat in contrast with the results from Roop's group [24,31], who showed that, in vivo siRNA for TAp63 produced a dramatic phenotype, with failure to organize pluristratified epithelia but no significant effect was observed on the basal layer. However, in our model [27] we investigated the role in early development using a genetically pure model, with the total absence of one isoform, the elegant in vivo study by Roop using siRNA addressed a slightly different question, representing a model of isoform unbalance.…”
Section: Differential Function Of P63 Isoforms In Epidermal Formationmentioning
confidence: 66%
See 2 more Smart Citations
“…In developmentally mature keratinocytes, p63 is required for both the proliferative and differentiation potential of these cells, and a subset of p63 targets are involved in the major signaling pathways for epithelial differentiation such as the Notch, Wnt and TGFb pathways. 32,10 Though little is known about the biological functions of TRAF4, our results indicate that the localization of the TRAF4 protein is associated with histological differentiation of SCCHN and that p63 cooperating with TRAF4 might be involved in the kerati- nocyte differentiation pathway. Since TRAF4 is also transactivated by p53 and TAp73, and as p53 family members are known to interact physically and functionally, 33,34 the in vivo regulation of TRAF4 expression is highly complex and tissue specific.…”
Section: Discussionmentioning
confidence: 75%